Structuring and organizing interprofessional healthcare in partnership with patients with diabetes: the INterprofessional Management and Education in Diabetes care (INMED) pathway. Issue 2 (4th March 2023) - Layani, Géraldine; Vachon, Brigitte; Duhoux, Arnaud; Lussier, Marie-Thérèse; Gil, Julian; Brault, Isabelle; Vanier, Marie-Claude; Rodrigues, Isabel; Motulsky, Aude; Kaczorowski, Janusz; David, Pierre-Marie; Battaglini, Alex
ABSTRACT: Type 2 diabetes is a complex chronic disease that requires ongoing monitoring by an interprofessional team to prevent complications. The INMED (INterprofessional Management and Education in Diabetes) care pathway was developed by our team to optimize primary care services for these patients and their families. The objective of this study is to describe the preliminary results of its adoption and implementation. The INMED care pathway is organized into four axes: (a) continuing professional education, (b) self-management support, (c) case management, and (d) ongoing evaluation of the quality of diabetes care and services. A multiple-case study is underway to document its effects on practice change using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework. Preliminary results on the adoption and implementation revealed some strengths: (a) regular patient follow-up by the case manager, (b) scheduling of physician appointments when required, and (c) regular screening for risk factors. Barriers were also identified: (a) lack of clear understanding of the case manager role, (b) lack of referrals to team members, and (c) lack of use of the motivational interview approach. The INMED care pathway is being adopted by primary care teams but challenges need to be overcome to improve its reach and effectiveness.